2022
DOI: 10.7554/elife.71437
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ligase Thin controls homeostatic plasticity through neurotransmitter release repression

Abstract: Synaptic proteins and synaptic transmission are under homeostatic control, but the relationship between these two processes remains enigmatic. Here, we systematically investigated the role of E3 ubiquitin ligases, key regulators of protein degradation-mediated proteostasis, in presynaptic homeostatic plasticity (PHP). An electrophysiology-based genetic screen of 157 E3 ligase-encoding genes at the Drosophila neuromuscular junction identified thin, an ortholog of human tripartite motif-containing 32 (TRIM32), a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…PatchSeq suggests unique post-translational modifications (PTMs) impact synaptic development in a cell-type-specific manner as several DEGs regulate sialylation and ubiquitination, with disruption to their function altering synaptic growth (Figure 4). Previously described SiaT mutants (Repnikova et al, 2010) and CG9003 RNAi knockdown lines (Baccino-Calace et al, 2022;Meltzer et al, 2019) showed reductions in NMJ evoked responses, indicating a functional role for sialylation and ubiquitination. SiAT mutants displayed reduced AZ number (p<0.0001, Figure 5A) and synaptic area (p<0.0001, Figure 5B) at Ib NMJs compared to controls or mutant Is NMJs (Figure 5A-C), indicating a preferential role for sialylation in arbor growth of tonic MNs.…”
Section: Distinct Post-translational Modifications Regulate Diversity...mentioning
confidence: 84%
“…PatchSeq suggests unique post-translational modifications (PTMs) impact synaptic development in a cell-type-specific manner as several DEGs regulate sialylation and ubiquitination, with disruption to their function altering synaptic growth (Figure 4). Previously described SiaT mutants (Repnikova et al, 2010) and CG9003 RNAi knockdown lines (Baccino-Calace et al, 2022;Meltzer et al, 2019) showed reductions in NMJ evoked responses, indicating a functional role for sialylation and ubiquitination. SiAT mutants displayed reduced AZ number (p<0.0001, Figure 5A) and synaptic area (p<0.0001, Figure 5B) at Ib NMJs compared to controls or mutant Is NMJs (Figure 5A-C), indicating a preferential role for sialylation in arbor growth of tonic MNs.…”
Section: Distinct Post-translational Modifications Regulate Diversity...mentioning
confidence: 84%
“…The PTPN11 N308D GoF mutants and csw 5 LoF nulls show stronger maintained EJC amplitudes over time and prolonged resistance to depression (Figs 3A and S7A ). RRP size was calculated by dividing the cumulative EJCs during the first 100 responses by mean mEJC amplitudes [ 39 ]. There is a sustained elevated response in both LoF and GoF mutants ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Synaptic events can also be recorded at synapses of the peripheral nervous system. We next applied miniML to analyze data obtained from the Drosophila melanogaster larval neuromuscular junction (NMJ) (Baccino-Calace et al, 2022). This synapse is characterized by a higher frequency of spontaneous synaptic events with a slower time course compared with typical brain slice recordings.…”
Section: Resultsmentioning
confidence: 99%
“…We used datasets from previous publications to generate training sets and to assess the application of miniML in zebrafish and Drosophila (Baccino-Calace et al, 2022; Delvendahl et al, 2019; Rupprecht and Friedrich, 2018). In addition, a published dataset (A.…”
Section: Methodsmentioning
confidence: 99%